2014 iAREA campaign on aerosol in Spitsbergen – Part 2: Optical properties from Raman-lidar and in-situ observations at Ny-Ålesund. (September 2016) - Ritter, C.; Neuber, R.; Schulz, Alexander; Markowicz, K.M.; Stachlewska, I.S.; Lisok, J.; Makuch, P.; Pakszys, P.; Markuszewski, P.; Rozwadowska, A.; Petelski, T.; Zielinski, T.; et al.
Abstract: In this work multi wavelength Raman lidar data from Ny-Ålesund, Spitsbergen have been analysed for the spring 2014 Arctic haze season, as part of the iAREA campaign. Typical values and probability distributions for aerosol backscatter, extinction and depolarisation, the lidar ratio and the color ratio for 4 different altitude intervals within the troposphere are given. These quantities and their dependencies are analysed and the frequency of altitude-dependent observed aerosol events are given. A comparison with ground-based size distribution and chemical composition is performed. Hence the aim of this paper is to provide typical and statistically meaningful properties of Arctic aerosol, which may be used in climate models or to constrain the radiative forcing. We have found that the 2014 season was only moderately polluted with Arctic haze and that sea salt and sulphate were the most dominant aerosol species. Moreover the drying of an aerosol layer after cloud disintegration has been observed. Hardly any clear temporal evolution over the 4 week data set on Arctic haze is obvious with the exception of the extinction coefficient and the lidar ratio, which significantly decreased below 2 km altitude by end April. In altitudes between 2 and 5 km the haze season lasted longer and the aerosol properties were generally more homogeneous than closer to the surface. Above 5 km only few particles were found. The variability of the lidar ratio is discussed. It was found that knowledge of the aerosol's size and shape does not determine the lidar ratio. Contrary to shape and lidar ratio, there is a clear correlation between size and backscatter: larger particles show a higher backscatter coefficient. Highlights: Temporal evolution of aerosol properties was relatively small. Moderate lidar rations around 30sr–50sr were found. The variability in extinction and lidar ratio is larger than in backscatter. The lidar ratio is neither correlated to the shape nor the size of the aerosol. Two regimes with β aer larger or smaller 1 Mm −1 sr −1 could be distinguished.